TEACHING OF A FOREIGN LANGUAGE AS A MEANS OF COMMUNICATION (Academia Science Repository, 2023)
Proficiency in a foreign language as a means of communication requires the ability to navigate in a particular situation, as well as to find the most effective ways and means of solving emerging problems, to predict the results of one's educational and communicative activities, i.e. active mental activity of the subject is required. Therefore, the teacher faces the need to search for such forms that would allow solvin g the whole complex of educational and methodological problems.